Lukisan Wayang Kamasan Sebagai Salah Satu Elemen Dekorasi Interior untuk Memberi Nuansa Bali yang Unik - Made Ida Mulyati; I Ketut Sudiana (Journal on Education, 2022)
Decoration elements are the most calculated elements in interior design to provide aesthetic value to a space. While the reality is that there are still many interior interior designers who have not been able to choose and quarter the right decoration elements based on the concept of space and the function of space. For this reason, it is necessary to study the decoration elements in interior design in accordance with the concept, function, and character of the desired space. Kamasan puppet painting is one of the traditional arts that has a strong and unique philosophy. The Kamasan puppet painting that symbolizes Dewi Semara Ratih pelambang beauty of true love is very suitable to be implemented in the interior of the master bedroom. Kamasan's puppet painting that tells the story of Prabu Kresna as Arjuna's coachman, during the Kurusetra Mahabharat war, is very suitable to be implemented in the interiors of schools, campuses, offices, libraries, and study rooms in residential buildings. Kamasan Dewi Saraswati's puppet painting is very suitable to be implemented in the interior of schools, campuses, offices, libraries and spaces used for work that are related to education. It is recommended for interior designers to make Kamasan puppet painting as an alternative as an element of decoration in the designed interior. In addition to giving a unique feel to the interior that is designed, it is also able to serve as a stakeholder to preserve traditional Balinese art.